Poly (vinyl alcohol)-oligophosphonate eco-friendly composites with improved reaction-to-fire properties. (December 2020) - Serbezeanu, Diana; Vlad-Bubulac, Tăchiță; Hamciuc, Corneliu; Hamciuc, Elena; Grădinaru, Luiza Mădălina; Lisa, Gabriela; Anghel, Ion; Şofran, Ioana-Emilia; Mocioi, Ionel-Alin; Enache, Alexandru Alin
Abstract: Flame retardation of poly (vinyl alcohol) with oligophosphonates, either as singular flame retardant filler or in the presence of intumescent additives, is a key to achieving eco-friendly advanced composites with improved reaction-to-fire properties. Herein, following a facile synthetic approach, PVA/oligophosphonate/ammonium sulfate composites were prepared via casting method. It was demonstrated that a low content of phosphorus led to composites exhibiting improved flame retardant properties. The peak heat release rate was substantially reduced in all the cases, depending on the content of oligophosphonates-based flame retardants or ammonium sulfate intumescent additive. Thermogravimetric data showed that the incorporation of the flame retardant significantly increased the phosphorus-rich char yield at elevated temperature.